Aktivitas Public Relations Bisnis Kampus Institut Bisnis Muhammadiyah (IBM) Bekasi - Lestari, Ayu Ria; El Adawiyah, Sa’diyah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This research aims to gather information about the activities of Business Public Relations (PR) at IBM Bekasi Campus. The method used in this research employs qualitative methods with data collection techniques through in-depth interviews with informants, document examination, observation, and data analysis, including observation, data reduction, and data presentation. The results of this study indicate that the Internal and External Public Relations (PR) activities at IBM Bekasi Campus emphasize the crucial role of PR in shaping a positive image, strengthening internal relationships, and increasing engagement with external parties. Internal PR focuses on fostering corporate culture, effective communication, and increasing employee engagement, while External PR emphasizes innovative promotional strategies, effective communication with the public, and strategic partnerships with industries. Both complement each other in creating a strong campus identity. Two-way communication, recognition of employee contributions, and engagement development strategies in Internal PR have a positive impact on the work environment and productivity. Meanwhile, External PR successfully creates the campus's appeal through various communication channels, active participation in educational events, and the use of social media as a promotional tool. Alumni involvement and responses to public feedback indicate adaptation that is relevant to technological developments and communication trends. The overall PR activities at IBM Bekasi Campus create a dynamic ecosystem, strengthen internal foundations, and open opportunities for sustainable partnerships, maintaining solid relationships with various stakeholders, and attracting prospective students.